The role of HDAC11 in age-related hearing loss: Mechanisms and therapeutic implications - Guan Lina; Chen Jing; Jiang Hongqun (Open Life Sciences, 2025)
This study focuses on the critical role of HDAC11 in age-related hearing loss and its underlying mechanisms. Through cellular experiments, we deeply explored the effects of HDAC11 on the proliferation and senescence of HEI-OC1 cells. The results showed that HDAC11 overexpression significantly reduced the acetylation level of α-microtubule protein, which in turn affected the stability of microtubule structure and accelerated the apoptosis and senescence process of HEI-OC1 cells. In addition, the overexpression of HDAC11 inhibited the Pink1/Parkin signaling pathway, which impeded the mitochondrial autophagy process and ultimately led to mitochondrial dysfunction. In animal experiments, we further verified the ameliorative effect of HDAC11 overexpression on hearing loss in aged mice. The experimental results showed that HDAC11 overexpression not only attenuated the histopathological damage of the cochlea in aged mice but also effectively improved their hearing function. Notably, HDAC11 overexpression suppressed the expression of cellular autophagy-related proteins and Pink1 and Parkin proteins. In summary, the present study preliminarily revealed that HDAC11 may regulate mitochondrial autophagy by inhibiting the Pink1/Parkin pathway, thus providing a new theoretical basis for improving hearing loss in the elderly.